Rare and potentially pathogenic variants in hydroxycarboxylic acid receptor genes identified in breast cancer cases - Cierla McGuire Sams; Kasey Shepp; Jada Pugh; Madison R. Bishop; Nancy D. Merner (BMC, 2021)
Abstract Background Three genes clustered together on chromosome 12 comprise a group of hydroxycarboxylic acid receptors (HCARs): HCAR1, HCAR2, and HCAR3. These paralogous genes encode different G-protein coupled receptors responsible for detecting glycolytic metabolites and controlling fatty acid oxidation. Though better known for regulating lipid metabolism in adipocytes, more recently, HCARs have been functionally associated with breast cancer proliferation/survival; HCAR2 has been described as a tumor suppressor and HCAR1 and HCAR3 as oncogenes. Thus, we sought to identify germline variants in HCAR1, HCAR2, and HCAR3 that could potentially be associated with breast cancer risk. Methods Two different cohorts of breast cancer cases were investigated, the Alabama Hereditary Cancer Cohort and The Cancer Genome Atlas, which were analyzed through nested PCRs/Sanger sequencing and whole-exome sequencing, respectively. All datasets were screened for rare, non-synonymous coding variants. Results Variants were identified in both breast cancer cohorts, some of which appeared to be associated with breast cancer BC risk, including HCAR1 c.58C > G (p.P20A), HCAR2 c.424C > T (p.R142W), HCAR2 c.517_518delinsAC (p.G173T), HCAR2 c.1036A > G (p.M346V), HCAR2 c.1086_1090del (p.P363Nfs*26), HCAR3 c.560G > A (p.R187Q), and HCAR3 c.1117delC (p.Q373Kfs*82). Additionally, HCAR2 c.515C > T (p.S172L), a previously identified loss-of-function variant, was identified. Conclusions Due to the important role of HCARs in breast cancer, it is vital to understand how these genetic variants play a role in breast cancer risk and proliferation and their consequences on treatment strategies. Additional studies will be needed to validate these findings. Nevertheless, the identification of these potentially pathogenic variants supports the need to investigate their functional consequences.